Main Visual Analysis of Extra Joyful Promotional Media 2025 in Increasing Participation in Customer Loyalty Program - Hudaya, Dedy Tri (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Extra Happy is a loyalty program for customers who have Telkomsel Points. The Extra Happy program offers extra internet quota with different amounts. Customers who make purchases of credit, data, video, games, international roaming and obtain Telkomsel Points have the opportunity to participate in exchanging Points for extra quota. This program is offered routinely during certain periods and has many variations. This aims to maintain loyalty and be able to utilize the Points owned without having to expire. By collecting many Points, you will have a great opportunity to get extra internet quota. Customer loyalty is the main thing to keep using Telkomsel products and utilize the Points owned by exchanging them for special programs.